How voice shapes reactions to impartial decision makers: An experiment - Marco Kleine; Pascal Langenbach; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2013)
We study how participation in decision processes shapes people's behavior towards impartial authorities. In an incentivized laboratory experiment, an impartial decision maker at first decides about the allocation of money between two subordinates. Treatments differ in the opportunity for one subordinate to state her opinion about the allocation before the decision is made (voice). We elicit the subordinate's attitude towards the impartial decision maker in a subsequent dictator game. Voice substantially increases transfers in the dictator game towards the former decision maker. Average transfers are 90% higher in voice treatments than in baseline. These positive voice effects occur irrespectively of the previous allocation decision by the impartial decision maker. Our results therefore stress the positive effects of participation in decision procedures when people interact with impartial authorities.
Keywords: D23; K40; C91; D03; 330; fairness; communication; voice; procedure; impartial decision maker; participative decision making; laboratory experiment